Peningkatan Kompetensi Guru dalam Penyusunan RPM Kurikulum Merdeka Berbasis Deep Learning di SD IT Al-Markazul Islami - Mutia Fonna; Iryana Muhammad; Mursalin, Mursalin; Hayatun Nufus; Nur Elisyah (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
The implementation of the Merdeka Curriculum requires teachers to possess adequate competence in developing contextual and meaningful Madrasah Lesson Plans (RPM). One of the main challenges lies in teachers’ ability to integrate deep learning approaches into instructional planning. This community service program aimed to enhance the competence of teachers at SD IT Al-Markazul Islami in developing deep learning–based Merdeka Curriculum lesson plans. The program employed a structured and participatory approach through training and mentoring activities, including conceptual presentations, group discussions, and hands-on practice in lesson plan development. Evaluation was conducted using a competence questionnaire administered to 20 participating teachers in the pretest and posttest stages. The data were analyzed descriptively. The results indicated that teachers’ competence scores in the pretest ranged from 54 to 63, with a mean score of 58.7, which fell into the moderate category. Following the intervention, posttest scores increased to a range of 89–97, with a mean score of 92.9, categorized as high. The improvement in scores ranged from 33 to 35 points for each participant. These findings demonstrate that the training and mentoring activities were effective in enhancing teachers’ competence in developing lesson plans aligned with the principles of the Merdeka Curriculum and deep learning approaches.